Language errors in the use of English by two different dialect groups of Afrikaans first language-speakers employed by Nedbank : an analysis and possible remedy - Coetzee, Wena (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (General Linguistics))--University of Stellenbosch, 2009.